Striatal Dopamine and the Interface between Motivation and Cognition - Aarts, Esther; van Holstein, Mieke; Cools, Roshan (Frontiers in Psychology, 2011)
Brain dopamine has long been known to be implicated in the domains of appetitive motivation and cognition. Recent work indicates that dopamine also plays a role in the interaction between appetitive motivation and cognition. Here we review this work. Animal work has revealed an arrangement of spiraling connections between the midbrain and the striatum that subserves a mechanism by which dopamine can direct information flow from ventromedial to more dorsal regions in the striatum. In line with current knowledge about dopamine's effects on cognition, we hypothesize that these striato-nigro-striatal connections provide the basis for functionally specific effects of appetitive motivation on cognition. One implication of this hypothesis is that appetitive motivation can induce cognitive improvement or impairment depending on task demands.